Marginal adaptation of inlay restorations designed by dental laboratory technician and dentist by using different intraoral digital scanners: in-vitro study - Asım, Emre (My University, 2019)
Amaç: Bu çalışmanın amacı iki farklı intraoral dijital tarayıcı kullanarak diş hekimi veya dişteknisyeni tarafından tasarlanarak üretilen inley restorasyonların marjinal ve internaluyumlarının in-vitro olarak araştırılmasıdır.Gereç ve Yöntem: Çalışmada periodontal sebeplerle çekilmiş 10 adet mandibular birinciküçük azı dişi kullanılarak, MOD sınıf 2 inlay preparasyonları diş hekimi tarafından yapılarakiki farklı intraoral dijital tarayıcı ve konvansiyonel ölçü ile ölçüler elde edilip deneyimli birdiş teknisyeni ve diş hekimi tarafından inlay restorasyonlar tasarlanmıştır. Çalışmada toplam5 grup oluşturulup toplam 50 örnek hazırlanmıştır(n=10). Istatistiksel analiz için SPSSprogramı kullanıldı.Bulgular: Çalışma sonucunda Cerec Omnicam ve Trios Pod ile tasarladığı restorasyonlarınmarjinal ve internal değerleri; konvansiyonel ölçu ile elde edilen restorasyonlarındeğerlerinden istatistiksel olarak daha iyi bulunmuştur (P<0.05). Teknisyen ve HekiminCerec Omnicam ve Trios Pod ile tasarladığı restorasyonlar arasında oklüzal ve intermarjinalbölgelerde istatistiksel olarak anlamlı fark bulunmuştur (P<0.05).Sonuç: Bu çalışmada bütün gruplardan elde edilen marjinal değerlerin klinik olarak kabuledilebilir olduğu bulunmuştur (<120 µm).

Aim: The aim of this in-vitro study was to examine the marginal and internal adaptations ofinlay restorations designed by a dentist or dental laboratory technician using two differentintraoral digital scanners.Material and Method: In this study, ten extracted mandibular first premolar teeth whichwere periodontally compromised was used. MOD class 2 Inlay preparations were prepared bythe dentist. The specimens were scanned using two different intraoral digital scanners andconventional impression. Inlay restorations were designed by an experienced dentallaboratory technician and dentist using both of the intraoral digital scanners. A total of 50specimens were prepared in a total of 5 groups (n=10). SPSS program was used for statisticalanalysis.Findings: The study results revealed a difference at the marginal and internal values of therestorations designed with both Cerec Omnicam and Trios Pod were found to be statisticallybetter than the restorations obtained with conventional impression (P<0.05). Statisticallysignificant difference was found at the occlusal and intermarginal regions of the restorationsdesigned by the dental laboratory technician and dentist using Cerec Omnicam and Trios Pod(P<0.05).Results: The marginal gap values obtained from all groups were clinically acceptable (<120µm).
Keywords: ceramic inlay; digital vs. conventional workflows; dijital ve konvansiyonel iş akışı; Direct digital scanning; Direkt dijital tarama; indirect digital scanning; indirekt dijital tarama; marginal gap; marjinal aralık; seramikinlay